E-COMMERCE ADOPTION BY SERVICE MSMES OF PUNE - et. al., Uma Parasuram (International Journal of Modern Agriculture, 2021)
With economic globalization and information technology development, e-commerce has now revolutionized how producers and consumers view the business. However, when compared with large companies, Micro, Small, and Medium Enterprises (MSMEs) adoption of e-commerce has not been satisfactory. The objective of the paper is to understand the adoption of e-commerce in MSMEs in Pune city and the barriers preventing further adoption of e-commerce. The research used a combination of structured web-based surveying and an unstructured interview-based case study analysis. The survey-form was sent to over 100 service-oriented small establishments in Pune, out of which 65 service enterprises responded. Enterprises were identified from the Udyog Aadhar registration directory. Sample MSMEs were from various service sectors, including publishing, education, consumer services, restaurants, etc. To form a deeper understanding of the extent and relevance of being online to businesses, the paper presents a comparative case study analysis to study e-commerce adoption in the IT and food and hospitality sector. The sample survey found that the average adoption of e-commerce was about 54%. Within the industry, firms have adopted varying levels of e-commerce. Smaller and newer firms within these sectors have shown greater adoption. The most significant barriers to e-commerce adoption were mindset shift towards e-commerce, preference for face-to-face transactions, cost of acquiring skilled workers, and changes in government policies that make the process expensive and tedious. Paper strongly advocates increased integration of e-commerce for small enterprises to improve efficiency and productivity and provides insight towards increasing the level of adoption for MSMEs in Pune